The Relationship Between University Students' Nutritional Status, Cardio-Metabolic Biomarkers and Physical Activity Levels - GÜNEŞ, FATMA ESRA; İÇEN, HAYRUNİSA (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: This study aimed to evaluate the relationship between nutritional status, cardiometabolic biomarkers and physical activity levels in university students. Methods: Firstly, fasting plasma total cholesterol, triglyceride, high-density lipoprotein cholesterol (HDL-C) levels were analyzed from participants' blood samples, and the homeostatic model assessment of insulin resistance (HOMA-IR) values were calculated after measuring fasting plasma glucose and insulin. Participants' weight, height, percentage of body fat, waist and hip circumference were measured and body mass index (BMI) was calculated. The International Physical Activity Questionnaire (IPAQ)and a questionnaire on socio-demographic characteristics were applied to participants. Energy and nutrient intakes were calculated from participants'24-hour dietary recall records. The statistical analysis of data was performed with SPSS version 21 software. For statistical significance, the total type-1 error level was determined as 5%. Results: Most of the participants' energy, dietary fibre, vitamins D and B1, folate, calcium and iron intakes were below recommended levels. HDL-C level was shown to be negatively correlated with total fat and saturated fatty acid intake (p<0.05). Omega-3 intakes of participants were negatively correlated with fasting plasma insulin and HOMA-IR (p<0.05).HDL-C was negatively correlated with BMI and waist-to-hip ratio, while fasting plasma insulin, triglyceride levels and HOMA-IR values were positively correlated with them (p<0.05). According to the IPAQ, it was found that 15.9% of participants had a low level of physical activity and 66.1% of them had a moderate level of physical activity. Conclusion: It is concluded that providing nutrition education and counselling services to students, improving campus facilities for physical activity are necessary for cardiometabolic health.
Keywords: University students; nutritional status; biomarkers; exercise; health; AGE